Pasar Valuta Asing - Andhika Pratama; Tasya Haenilah; Amar Azhari; Feronica Simanjorang (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Currency transactions require justification in the study of Fiqh Muamalah because the buying and selling of foreign currencies is very closely related to the functioning of the world economy and cannot be separated. Foreign currency is foreign currency such as US dollars, pounds, ringgit, and others. Efficient currency markets mean that future changes in exchange rates are unpredictable. The marketing activities of an international company are often organized as a separate and independent function within the company.